The oldest Cambrian trilobite – brachiopod association in South China - Zhang, Zhiliang; Ghobadi Pour, Mansoureh; Popov, Leonid E.; Holmer, Lars E.; Chen, Feiyang; Chen, Yanlong; Brock, Glenn A.; Zhang, Zhifei (Gondwana Research, 2021)
Limestones of the Xihaoping Member of the Dengying Formation in the Xiaoyangba section, South China, yield the oldest known Cambrian brachiopod–trilobite association. In this member, the trilobite Parabadiella cf. huoi co-occurs with the new brachiopod species Eoobolus incipiens sp. nov. The association provides potential for correlation of lower Cambrian successions and gives novel insights into the origin, palaeobiogeographic distribution and early evolution of linguliform brachiopods. Parabadiella occurs in shallow marine clastic and carbonate rocks in South China, demonstrating a broad distribution for this taxon. The new discovery indicates an early Chiungchussuan age ( Parabadiella trilobite Zone, Cambrian Age 3) for the longstanding problematic Xihaoping Member. Furthermore, this earliest Parabadiella–Eoobolus association helps to establish close links with the oldest known trilobite–brachiopod assemblage from the upper Micrina etheridgei Zone ( Parabadiella huoi trilobite Zone) in Australia. Eoobolus incipiens represents one of the earliest known linguliform brachiopods, with a distinctive mixture of characters shared with both problematic tommotiids, as well as paterinide, lingulide and acrotretide brachiopods, indicating that these features may be plesiomorphic for the Linguliformea. An age-constrained dispersal mode for early lingulate brachiopods is proposed, indicating that the Subphylum Linguliformea may have originated in East Gondwana and South China during Cambrian Age 3, and only subsequently dispersed to other major Cambrian palaeocontinents (e.g. Siberia, Laurentia, Antarctica, Baltica, Avalonia, West Gondwana, North China) during the late stage of the Cambrian evolutionary radiation of animals.